Evaluation of impacted maxillary canine position using panoramic radiography and cone beam computed tomography - Wafa Alfaleh; Sarah Al Thobiani (Saudi Dental Journal)
Introduction: Localization of impacted maxillary canine (IMC) position is essential in orthodontic treatment for accurate orthodontic treatment as well as prognosis. Objectives: This study aimed to: 1- investigate the relationship between the locations of IMC in panoramic radiograph (PR) using sectors in relation to their labio-palatal position in cone beam computed tomography (CBCT): 2- report the incisor root resorption in CBCT in relation to its sector location of IMC in PR. Material and Methods: The study is a retrospective imaging assessment of 60 IMCs in multiple centers in Riyadh, Saudi Arabia. Sector location of IMC was determined on the PR and correlated with each of their labio-palatal positions and resorption of the root of permanent incisors using CBCT. Results: There is a significant correlation between sector location and impaction location of IMC. No statistical correlation was found between IMC sector location and lateral incisor root resorption, whereas a significant correlation was found between sector location and central incisor root resorption. Conclusions: For Sectors I and II, IMC tended to be in either the mid-alveolus or labial location, whereas Sectors III and IV tended to show palatal impaction. Therefore, sector could be a good tool for localization of IMC and to predict the possibility of incisor root resorption.